Evaluation of dryland maize / pigeonpea intercropping under variable phosphorus application rates - Nndwambi, F. H. (University of Limpopo, 2015)
Information on the performance of the maize and pigeonpea intercropping system under dryland conditions of South Africa is scanty. The aim of this study was to determine the optimum P level and productivity of pigeonpea and maize under the dryland intercropping system. Five P rates (0, 15, 30, 45, and 60 kg P ha-1) were applied to both sole and pigeonpea intercropped with maize in a randomized complete block design with 4 replicates. Growth parameters and yield and yield attributes of pigeonpea and maize were measured to determine performance of both crops. There were significant differences in grain yield of pigeonpea as influenced by P rates in both seasons. Highest grain yields of 781 kg ha-1 during 2009/10 and 894 kg ha-1 during 2010/11 were obtained at P rate of 45 kg ha-1. Cropping system significantly influenced grain yield of pigeonpea in 2010/11 season with 37.1% higher pigeonpea grain yield from intercropped plots than in sole pigeonpea plots. There was 21.8% increase in grain yield of pigeonpea across two seasons as influenced by P rate. Maize grain yield showed little response to P rate only during the first season. However, highest maize grain yield of 1699 kg ha-1 was obtained at 60 kg P ha-1 during the 2009/10 season. Maize grain yield was only significantly influenced by cropping system during the 2010/11 season where sole plots achieved higher grain yield of 4148 kg ha-1 compared to 3297 kg ha-1 from intercrop plots. The results revealed that P application increased grain yield of pigeonpea significantly, especially in intercropped plots. The calculated total land equivalent ratio (LER) for the two crops gave positive and higher than one values, which suggests a favourable grain yield advantage for maize/pigeon pea intercrop.
Thesis (M.Sc (Plant Production)) --University of Limpopo, 2015
Keywords: Pigeonpea; Intercropping; Maize; Grain yield; Phosphorus rates; Dryland; 631.586; Dry farming -- South Africa; Corn -- Breeding